Congenital Hemophagocytic Lymphohistiocytosis Presenting as Thrombocytopenia in a Newborn. Issue 4 (May 2015) - Hinson, Ashley; Owen, William; Prose, Neil; Parikh, Suhag; Thornburg, Courtney
<x xml:space="preserve">Abstract</x> Hemophagocytic lymphohistiocytosis (HLH) is a disease caused by dysregulation and hyperactivation of the immune system, and can be familial or acquired. HLH presenting in infancy can be rapidly fatal if not promptly recognized and treated. Congenital HLH can be caused by various genetic mutations or part of immunodeficiency syndromes. We present an infant with Griscelli syndrome and familial HLH with atypical genetic mutations, presenting as thrombocytopenia on the first day of life, cured with chemotherapy and unrelated cord blood transplant.